(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
First, the article provides general information about the history of the development of small industrial enterprises. Then, how to provide the analysis of the development of small industrial enterprises will be explained. At the same time, the main attention is paid to effective solutions for the development of small industrial enterprises working in these fields.